Dans Paris - Honoré, Christophe, 1970-; Duris, Romain, 1974-; Garrel, Louis; Marchand, Guy, 1937- (Gemini Films, 2006)
Paul, depressed from his recent break-up with Anna, returns home to live with his divorced father and womanizing, slacking younger brother, Jonathan. With little success, his carefree sibling and doting father try to cheer him up with women, wine, and home-cooked meals. When, in the midnight hour, Paul is forced to entertain one of his brother's desperate girlfriends, he begins to realize that while things never go according to plan, family and the pursuit of love are always worth the fight.